Informação, aprendizagem, conhecimento: a tríplice aliança no contexto da educação a distância - Jose Wilson da Costa (2002)
Distance education (learning) has become a reality in contemporary society. New information and communication technologies continue to expand the number of pedagogical possibilities for both student and techer (instructor). The current investigation of distance education reflects a scientific orientation that perceives man as a social being who learns through relations with others, large cultural influences are also explored. Futhermore, human cognition is examined through an ecological framework where information and knowledge are, at the same time, source and product of knowing. Specifically, this work inquiry examines a distance learning course offered by PUC Minas Virtual that implements new information and communication technologies with the objective of furthering this educational modality and providing evidence for is efficacy. The research paradigm utilized was observational in nature. It analyze, through multiple perspectives, both the teaching and learning process involved in distance learning and was established in theories of learning in compliance with a constructivism conception of the knowledge. The current investigation seeks to provide readers with relatively new methodology of education in the modalities of distance courses.